2000
DOI: 10.1002/(sici)1521-4109(200002)12:3<199::aid-elan199>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

Voltammetric Determination of Nitrates Using Silver Electrodes

Abstract: A silver disk electrode (diameter 0.2 mm) and composite silver electrode prepared from a mixture of silver, graphite powder and methacrylate resin (20 % Ag, 20 % graphite, 60 % methacrylate resin) are described. The electrodes prepared were used for the voltammetric determination of nitrate ions in samples of natural and wastewater (detection limit 7 mg L 71). The activation of the electrode surface before each measurement by a time-de®ned polarization ensures the reproducibility of the results of the voltamme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
2

Year Published

2003
2003
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 22 publications
0
26
0
2
Order By: Relevance
“…silver) electrode 5,9 . As the graphite solid composite electrodes do not contain any mercury, they present (as well as metallic composite 1,5,8,[10][11][12][13][14]32 , metallic 26,33,34 , solid amalgam and solid composite amalgam electrodes 9,35-39 ) an acceptable electrode material in all analytical laboratories.…”
Section: Discussionmentioning
confidence: 99%
“…silver) electrode 5,9 . As the graphite solid composite electrodes do not contain any mercury, they present (as well as metallic composite 1,5,8,[10][11][12][13][14]32 , metallic 26,33,34 , solid amalgam and solid composite amalgam electrodes 9,35-39 ) an acceptable electrode material in all analytical laboratories.…”
Section: Discussionmentioning
confidence: 99%
“…Among many electrode materials, copper is expected to be the most effective material in terms of electroreduction of nitrate and nitrite ions. [15][16][17][18][19][20][21] Indeed, many studies have shown that pretreated and/or modified copper electrodes are effective for the determination of nitrate and nitrite ions. 13,14,[22][23][24][25][26] However, the pretreatments and/or modifications of copper electrodes in the studies seem to be complicated, time consuming and insufficiently sensitive for the determination of nitrate and nitrite ions in natural water samples.…”
Section: Introductionmentioning
confidence: 99%
“…(8) Information from cloud server or social platform could also be retrieved to smart phone for analysis. at −1.5 V. This activation process will remove the possible oxidation layer at the surface of working electrode [20,21,35]. In order to avoid oxidation of silver working electrode and to make nitrate reduction happen, the sweeping voltage between working and reference electrode is chosen from 0 V to −1.5 V with a sweeping rate of 100 mV/s for cyclic voltammetry testing.…”
Section: Cyclic Voltammetry Methodsmentioning
confidence: 99%
“…4(a), which shows a linear relationship with concentration. The fact that the peak potential is more negative compared with previous experiments from other research groups [15,16,35,36] can be attributed to more positive standard reduction potential of the reference electrode. This current peak is caused by the reduction of nitrate since the peak value increases with the increase of nitrate concentration.…”
Section: Miniaturized Nitrate Sensor Characterizationmentioning
confidence: 99%